THE EFFECT OF TRANSPARATION, ACCOUNTABILITY, COMMUNITY PARTICIPATION, INTERNAL CONTROL AND VILLAGE GOVERNMENT ACCOUNTING COMPETENCE ON COMMUNITY EMPOWERMENT IN BETAK VILLAGE KALIDAWIR TULUNGAGUNG - Muhammad Syahrul Hidayat; Elok Rafika Sari (State Islamic Institute (IAIN) Tulungagung, 2021)
The purpose of this research is to analyze the influence of transparency, accountability, community participation, internal control and accounting competence on the empowerment of the Betak village community simultaneously and partially using multiple linear regression. The test method was carried out using primary data by distributing questionnaires and then analyzed using the SPSS 16 application. The results of this study indicate that partially there are two variables that have a significant effect on community empowerment, namely accountability and community participation, while the other three variables have no effect. Meanwhile, the variables of transparency, accountability, community empowerment, internal control and accounting competence simultaneously affect community empowerment with a total effect of 85.3%.